Comparison of the machinability of the 316L and 18Ni300 additively manufactured steels based on turning tests. (October 2021) - Silva, Tiago EF; Amaral, Ana; Couto, André; Coelho, João; Reis, Ana; Rosa, Pedro AR; Jesus, Abílio MP de
This paper focuses on the machinability of additively manufactured steel alloys (316L stainless steel and 18Ni300 Maraging steel) by reference to their conventional metallurgical conditions. The machinability of both metallurgical conditions has been evaluated by longitudinal turning tests under laboratory conditions using two different cutting tool geometries (flat rake face and chip-breaker geometry) and covering different cutting speeds, depths of cut and feed values. Cutting forces, chip morphology and surface roughness were investigated as machinability indicators. The influence of chip-breaker on process performance was also analysed. For a comprehensive discussion of the results, microstructure, chemical composition, surface roughness and mechanical strength of both metallurgical conditions were studied. The paper quantitatively demonstrates that despite the higher mechanical strength of additively manufactured alloys, no significant power requirements were verified for the finishing cutting of tested alloys, when compared with conventional materials. Also noteworthy, is the surface quality improvement of the printed samples due to the most favourable conditions for chip formation. The usage of a chip breaker insert had higher impact on reducing required cutting energy than on controlling chip geometry.